Antioxidant response and related gene expression in aged oat seed - Kong, Lingqi; Huo, Heqiang; Mao, Peisheng (Frontiers in Plant Science, 2015)
To evaluate deterioration of oat seeds during storage, we analyzed oxygen radicals, antioxidant enzyme activity, proline content, and gene transcript levels in oat seeds with different moisture contents (4%, 16%, and 28% w/w) during storage for 0, 6, and 12 months (CK, LT-6, and LT-12 treatments, respectively) at 4 °C. The germination percentage decreased significantly with higher seed moisture contents and longer storage duration. The concentrations of superoxide radical and hydrogen peroxide increased with seed moisture content increasing. The activities of catalase (CAT), ascorbate peroxidase (APX), and superoxide dismutase (SOD) may have had a complementary or interacting role to scavenge reactive oxygen species. As the storage duration extended, the proline content decreased in seeds with 4% and 16% moisture content and increased in 28%. These findings suggest that proline played the main role in adaptation to oxidative stress in seeds with higher moisture content (28%), while antioxidant enzymes played the main role in seeds with lower moisture contents (4%, 16%). In the gene transcript analyses, SOD1 transcript levels were not consistent with total SOD activity. The transcript levels of APX1 and CAT1 showed similar trends to those of APX and CAT activity. The transcript levels of P5CS1, which encodes a proline biosynthetic enzyme, increased with seed moisture content increasing in CK. Compared with changing of proline content in seeds stored 12 months, PDH1 transcript levels showed the opposite trend and maintained the lower levels in seeds of 16% and 28% moisture contents. The transcript level of P5CS1 was significantly affected by moisture content, and PDH1 could improve stress resistance for seed aging and maintain seed vigor during long-term storage.